KOMUNIKASI ANTARBUDAYA DALAM KONFLIK DI MEDIA SOSIAL (CONTENT ANALYSIS KONFLIK OVERSTAY KRISTEN GRAY DI TWITTER) - Dimas Satriawan Lambang Wicaksono; Farah Fattatin Fauziah; Ulima Nabila Adinta; Lidwina Mutia Sadasri (Universitas Gadjah Mada, 2023)
Social media has become a place for various limitless interactions, including conflict interaction. This research is intended to discover the face management of individuals with different cultural backgrounds in intercultural conflict situations on social media. One of the issues that can be studied using the concept of face negotiation theory is the case of Kristen Gray’s overstay, which was discussed for several days on Twitter. Therefore, three research questions emerge: (1) how is face management between Indonesian citizens and Black Americans in the intercultural conflict